Understanding in-context interaction: An investigation into on-the-go mobile search. Issue 6 (November 2019) - Harvey, Morgan; Pointon, Matthew
Highlights: Mobile situational contexts (like walking) affect user behaviour and performance. Prevalence of use of different grip types varies depending on context. The combination of context and grip type impacts interaction performance and behaviour and incidence and type of different errors. Different grips are more effective in varying situational contexts. Abstract: Recent years have seen a profound change in how most users interact with search engines: the majority of search requests now come from mobile devices, which are used in a number of distracting contexts. This use of mobile devices in various situational contexts away from a desk presents a range of novel challenges for users and, consequently, possibilities for interface improvements. However, there is at present a lack of work that evaluates interaction in such contexts to understand what effects context and mobility have on behaviour and errors and, ultimately, users' search performance. Through a controlled study, in which we simulate walking conditions on a treadmill and obstacle course, we use a combination of interaction logs and multiple video streams to capture interaction behaviour as participants ( n = 24) complete simple search tasks. Using a bespoke tagging tool to analyse these recordings, we investigate how situational context and distractions impact user behaviour and performance, contrasting this with users in a baseline, seated condition. Our findings provide insights into the issues these common contexts cause, how users adapt and how such interfaces could be improved.